High-strength anti-corrosion electric circulating water pipeline reinforcing composite material and preparation method thereof

Through the preparation of reinforced composite materials for high-strength anti-corrosion power circulation water pipelines, the corrosion and mechanical stress problems of power circulation water pipelines are solved, efficient anti-corrosion and reinforcement effects are achieved, and the service life and safety of the pipelines are extended.

CN120535909APending Publication Date: 2025-08-26SHANDONG LANHAI NEW MATERIAL TECH CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510870245.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-26
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

Existing power circulating water pipelines face cracks and leakage caused by chemical corrosion, microbial corrosion, water flow erosion and mechanical stress. Traditional anticorrosion coatings and nanomodified materials have problems such as insufficient protection and low construction efficiency.

Method used

The composite material is reinforced with high-strength anti-corrosion power circulation water pipeline, including resin matrix, reinforcement fiber, anti-corrosion filler, coupling agent and curing agent. Through fiber mixing, resin matrix preparation, anti-corrosion filler and additive, an interpenetrating network structure is formed, combined with the synergistic effect of nanomaterials, a dense barrier and protective film are formed to resist mechanical and electrochemical corrosion.

Benefits of technology

It significantly improves the anti-corrosion performance and mechanical strength of the pipeline, extends the service life, reduces maintenance costs, and improves safety and operating reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120535909A_ABST
    Figure CN120535909A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer-based composite materials for pipeline corrosion prevention and reinforcement, and particularly relates to a high-strength corrosion-resistant electric circulating water pipeline reinforcement composite material and a preparation method thereof.The high-strength corrosion-resistant electric circulating water pipeline reinforcement composite material is prepared from, by mass, 40-60 parts of resin matrix, 30-50 parts of reinforcing fibers, 10-20 parts of corrosion-resistant filler, 0.5-1.5 parts of coupling agent, 5-10 parts of curing agent and 1-3 parts of auxiliaries; the preparation method comprises the steps of fiber pretreatment; preparing a resin matrix; adding an anti-corrosion filler and an auxiliary agent; preparing a composite material component I; preparing a composite material component II; and post-processing. The high-strength anti-corrosion electric power circulating water pipeline reinforcing composite material has high strength and excellent anti-corrosion performance, the problems of corrosion, damage and the like of an electric power circulating water pipeline can be effectively solved, the service life of the pipeline is prolonged, and the use safety is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer-based composite materials for pipeline anti-corrosion reinforcement, and specifically relates to a high-strength anti-corrosion composite material for reinforcing electric power circulating water pipelines and a preparation method thereof. Background Art

[0002] In the power industry, circulating water pipelines play a critical role in cooling power generation equipment and ensuring the stable operation of power systems. However, due to their long-term exposure to complex operating environments, they face numerous challenges. On the one hand, dissolved oxygen, acidic and alkaline substances, chloride ions, and microorganisms contained in circulating water can cause chemical corrosion, pitting corrosion, crevice corrosion, and microbial corrosion. Chloride ions, for example, can damage the passivation film on the pipe surface, and the biofilm formed by microbial growth can accelerate localized corrosion. On the other hand, the erosion caused by the flow of circulating water, especially at pipe elbows and reducers, can cause erosion and corrosion. Furthermore, thermal and mechanical stresses caused by temperature changes and pressure fluctuations can cause cracks, deformation, and even leaks in the pipelines. This not only wastes water resources, increases maintenance costs and downtime, but can also affect the normal operation of power generation equipment and lead to safety accidents.

[0003] The existing pipeline inner wall coating protection has obvious shortcomings: the traditional anti-corrosion coating protective layer is thin, has weak mechanical stress resistance, and is easily damaged; the anti-corrosion mortar has poor acid corrosion resistance and is prone to cracking and peeling; the preparation process of some nano-modified materials is complicated, the curing time is long, and the construction efficiency is low. Summary of the Invention

[0004] The purpose of the present invention is to provide a high-strength anti-corrosion composite material for reinforcing electric power circulating water pipelines and a preparation method thereof. The high-strength anti-corrosion composite material for reinforcing electric power circulating water pipelines has high strength and excellent anti-corrosion performance, can effectively solve the problems of corrosion and damage faced by electric power circulating water pipelines, extend the service life of the pipelines, and improve safety of use.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] The high-strength anti-corrosion composite material for reinforcing electric power circulating water pipelines comprises, by weight, 40-60 parts of a resin matrix, 30-50 parts of reinforcing fibers, 10-20 parts of anti-corrosion fillers, 0.5-1.5 parts of coupling agents, 5-10 parts of curing agents, and 1-3 parts of additives.

[0007] Optionally, the resin matrix is ​​a mixture of epoxy resin, vinyl ester resin, unsaturated polyester resin and fluorine-containing polyether polyimide resin solution, and the mass ratio is (2-3): (1-2): (1-2): (2-4).

[0008] Optionally, the preparation method of the fluorinated polyether polyimide resin solution is as follows: adding a fluorinated polyether diamine monomer and a dianhydride monomer to N-methylpyrrolidone, stirring and reacting at 80-100°C for 3-5 hours under nitrogen protection to obtain a polyamic acid solution; then heating the polyamic acid solution to 180-200°C, carrying out an imidization reaction for 6-8 hours to obtain a fluorinated polyether polyimide resin; finally, dissolving the fluorinated polyether polyimide resin in N-methylpyrrolidone to obtain a fluorinated polyether polyimide resin solution; the mass ratio of the fluorinated polyether diamine monomer, the dianhydride monomer and N-methylpyrrolidone is (1-2): (1.5-2): (1-2), and the mass ratio of the fluorinated polyether polyimide resin to N-methylpyrrolidone is (1-2): (2-3).

[0009] Optionally, the reinforcing fiber is a mixture of glass fiber, carbon fiber and aramid fiber, and the mass ratio is (3-4):(1-2):(1-2).

[0010] Optionally, the anti-corrosion filler is a mixture of nano-titanium dioxide, graphene and zinc powder, and the mass ratio is (2-3):(1-2):(3-4).

[0011] Optionally, the curing agent is a mixture of an amine curing agent, a peroxide curing agent and a special curing agent for a fluorinated polyether polyimide resin solution, and the mass ratio is (1-3):(2-3):(1-2); the amine curing agent is m-phenylenediamine, the peroxide curing agent is benzoyl peroxide, and the special curing agent for a fluorinated polyether polyimide resin solution is pyromellitic dianhydride.

[0012] Optionally, the coupling agent is a silane coupling agent, and the silane coupling agent is one or both of aminosilane and vinylsilane; the auxiliary agent includes an antioxidant, a flame retardant and a dispersant; the antioxidant is a combination of one or more of diphenylamine, p-phenylenediamine, and 2,6-tert-butyl-4-methylphenol; the flame retardant is a combination of one or more of magnesium hydroxide, ammonium polyphosphate, and triphenyl phosphate; the dispersant is a combination of one or more of sodium oleate, sodium polyacrylate, and polyvinyl alcohol.

[0013] The method for preparing the high-strength anti-corrosion composite material for reinforcing electric power circulating water pipelines as described in any one of the above items is characterized by comprising the following steps:

[0014] Fiber pretreatment: Mix glass fiber, carbon fiber and aramid fiber according to the mass ratio, soak them in 2-5% by mass silane coupling agent solution for 10-30 minutes, and dry them at 60-80℃ for 2-4 hours;

[0015] Preparation of resin matrix: adding epoxy resin, vinyl ester resin, unsaturated polyester resin and fluorinated polyether polyimide resin solution into a reaction kettle according to the mass ratio, stirring and mixing at 40-60° C. to obtain a resin matrix;

[0016] Adding anti-corrosion fillers and additives: Add nano titanium dioxide, graphene, zinc powder, antioxidant, flame retardant and dispersant to the mixed resin matrix according to the mass ratio, and stir at 60-80℃ for 1-2 hours;

[0017] Preparation of composite material component 1: slowly adding the pretreated mixed fiber into a resin matrix containing an anticorrosive filler and an additive, stirring at 10-25 r / min for 10-30 minutes to obtain composite material component 1;

[0018] Preparing the second composite material component: adding the curing agent and the coupling agent into the second reaction kettle according to the mass ratio and mixing them to obtain the second composite material component;

[0019] Post-processing: Degassing treatment is performed on the composite material component one and the composite material component two respectively.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention mixes glass fiber, carbon fiber, and aramid fiber in specific proportions, utilizing the rigidity of glass fiber, the high strength of carbon fiber, and the toughness of aramid fiber to form a "rigid and flexible" reinforcement system, so that the prepared composite material can effectively resist the mechanical stress and thermal stress during pipeline operation and prevent crack propagation. At the same time, a fluorinated polyether-type polyimide resin solution is introduced into the resin matrix, and its rigid imide rings and flexible fluorinated polyether segments form an interpenetrating network structure, further improving the matrix's deformation resistance and fatigue resistance, so that the composite material can maintain structural stability under long-term alternating loads.

[0022] 2. When performing physical barrier, the present invention utilizes the lamellae structure of graphene and the low surface energy characteristics of the fluorinated polyether polyimide resin solution to form a nano-scale dense barrier on the surface of the material, blocking the penetration path of corrosive media such as chloride ions and water molecules; when performing electrochemical protection, zinc powder is used as a sacrificial anode to form a protective film on the surface of the composite material through electrochemical action. Even if the coating is partially damaged, the zinc powder can still be oxidized and consumed to protect the pipeline matrix, thereby delaying the corrosion process; when performing chemical inhibition, the photocatalytic properties of nano-titanium dioxide can be used to inhibit the growth of microorganisms and destroy the formation of biofilms. Combined with the chemical corrosion resistance of vinyl ester resin, it can effectively resist the combined corrosion of dissolved salts and microorganisms in circulating water. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0024] Figure 1 This is a flow chart of the method for preparing the high-strength anti-corrosion composite material for reinforcing electric power circulating water pipelines of the present invention. DETAILED DESCRIPTION

[0025] Example 1

[0026] Weigh out by mass: 25 parts of epoxy resin, 12 parts of vinyl ester resin, 13 parts of unsaturated polyester resin, and 0.8 parts of fluorinated polyether polyimide resin solution as the resin matrix; 32 parts of glass fiber, 12 parts of carbon fiber, and 16 parts of aramid fiber as the reinforcing fiber; 8 parts of nano-titanium dioxide, 4 parts of graphene, and 8 parts of zinc powder as anti-corrosion fillers; 1 part of aminosilane; 6 parts of m-phenylenediamine, 2 parts of benzoyl peroxide, and 1 part of pyromellitic dianhydride; 0.8 parts of diphenylamine, 1 part of ammonium polyphosphate, and 1.2 parts of sodium polyacrylate as additives.

[0027] Preparation of a fluorinated polyether polyimide resin solution: First, a fluorinated polyether diamine monomer and a dianhydride monomer are added to N-methylpyrrolidone in a certain mass ratio; under nitrogen protection, the mixture is stirred and reacted at 90°C for 4 hours to generate a polycondensation reaction to form a polyamic acid solution; the polyamic acid solution is heated to 190°C and subjected to an imidization reaction for 7 hours to obtain a fluorinated polyether polyimide resin; finally, the fluorinated polyether polyimide resin is dissolved in N-methylpyrrolidone to prepare a fluorinated polyether polyimide resin solution with a solid content of 35%.

[0028] The preparation process is as follows:

[0029] Fiber pretreatment: glass fiber, carbon fiber and aramid fiber were mixed according to the mass ratio, soaked in 5% by mass silane coupling agent solution for 10 minutes, and dried at 60°C for 4 hours;

[0030] Preparation of resin matrix: adding epoxy resin, vinyl ester resin, unsaturated polyester resin and fluorinated polyether polyimide resin solution into a reaction kettle according to the mass ratio, and stirring and mixing at 40° C. to obtain a resin matrix;

[0031] Addition of anticorrosive fillers and additives: Add nano-titanium dioxide, graphene, zinc powder, diphenylamine, ammonium polyphosphate and sodium polyacrylate to the mixed resin matrix according to the mass ratio and stir at 60°C for 2 hours;

[0032] Preparation of composite material component 1: slowly adding the pretreated mixed fiber into a resin matrix containing an anticorrosive filler and an additive, stirring at 10 r / min for 15 minutes, to obtain composite material component 1;

[0033] Preparation of composite material component 2: adding m-phenylenediamine, benzoyl peroxide, pyromellitic dianhydride and aminosilane into the second reaction kettle according to the mass ratio and mixing them to obtain composite material component 2;

[0034] Post-processing: Degassing treatment is performed on the composite material component one and the composite material component two respectively.

[0035] When used for corrosion protection and reinforcement of power circulating water pipelines, the composite material component 1 and composite material component 2 prepared by the above method are first fully blended in a mass ratio of 1:1 to form a mixed composite material. The prepared mixed composite material is then evenly sprayed onto the inner wall of the pipeline by spraying. The pipeline is then placed in a curing oven for curing at 200°C for 2 hours, until the thickness of the mixed composite material covering the inner wall of the pipeline reaches 5mm, thereby achieving pipeline reinforcement.

[0036] Example 2

[0037] Weigh, by mass, the following: 28 parts of epoxy resin, 10 parts of vinyl ester resin, 12 parts of unsaturated polyester resin, and 0.9 parts of fluorinated polyether polyimide resin solution (prepared in the same manner as in Example 1) as a resin matrix; 35 parts of glass fiber, 10 parts of carbon fiber, and 15 parts of aramid fiber as reinforcing fibers; 9 parts of nano-titanium dioxide, 3 parts of graphene, and 8 parts of zinc powder as anticorrosive fillers; 1.2 parts of aminosilane; 6 parts of m-phenylenediamine, 7 parts of benzoyl peroxide, and 1.2 parts of pyromellitic dianhydride; 0.7 parts of diphenylamine, 1.1 parts of ammonium polyphosphate, and 1.2 parts of sodium ammonium polyacrylate as additives.

[0038] The preparation process is as follows:

[0039] Fiber pretreatment: glass fiber, carbon fiber and aramid fiber were mixed according to the mass ratio, soaked in 4% by mass silane coupling agent solution for 20 minutes, and dried at 70°C for 3 hours;

[0040] Preparation of resin matrix: adding epoxy resin, vinyl ester resin, unsaturated polyester resin and fluorinated polyether polyimide resin solution into a reaction kettle according to the mass ratio, and stirring and mixing at 40° C. to obtain a resin matrix;

[0041] Addition of anticorrosive fillers and additives: Add nano-titanium dioxide, graphene, zinc powder, diphenylamine, ammonium polyphosphate and sodium polyacrylate to the mixed resin matrix according to the mass ratio and stir at 70°C for 1.5 hours;

[0042] Preparation of composite material component 1: slowly adding the pretreated mixed fiber into a resin matrix containing an anticorrosive filler and an additive, stirring at 15 r / min for 20 minutes, to obtain composite material component 1;

[0043] Preparation of composite material component 2: adding m-phenylenediamine, benzoyl peroxide, pyromellitic dianhydride and aminosilane into the second reaction kettle according to the mass ratio and mixing them to obtain composite material component 2;

[0044] Post-processing: Degassing treatment is performed on the composite material component one and the composite material component two respectively.

[0045] When used for corrosion protection and reinforcement of power circulating water pipelines, the composite material component 1 and composite material component 2 prepared above are first fully blended in a mass ratio of 2:3 to form a mixed composite material. The prepared mixed composite material is then evenly sprayed onto the inner wall of the pipeline by spraying. The pipeline is then placed in a curing oven for curing at 200°C for 2 hours, until the thickness of the mixed composite material covering the inner wall of the pipeline reaches 5mm, thereby achieving pipeline reinforcement.

[0046] Example 3

[0047] Weigh, by mass, the following: 26 parts of epoxy resin, 11 parts of vinyl ester resin, 13 parts of unsaturated polyester resin, and 0.7 parts of fluorinated polyether polyimide resin solution (prepared in the same manner as in Example 1) as a resin matrix; 33 parts of glass fiber, 11 parts of carbon fiber, and 16 parts of aramid fiber as reinforcing fibers; 8 parts of nano-titanium dioxide, 4 parts of graphene, and 8 parts of zinc powder as anticorrosive fillers; 1.1 parts of aminosilane; 6.5 parts of m-phenylenediamine, 2.5 parts of benzoyl peroxide, and 0.9 parts of pyromellitic dianhydride; 0.8 parts of diphenylamine, 1.1 parts of ammonium polyphosphate, and 1.1 parts of sodium polyacrylate as additives.

[0048] The preparation process is as follows:

[0049] Fiber pretreatment: glass fiber, carbon fiber and aramid fiber were mixed according to the mass ratio, soaked in 3% by mass silane coupling agent solution for 30 minutes, and dried at 75°C for 3 hours;

[0050] Preparation of resin matrix: adding epoxy resin, vinyl ester resin, unsaturated polyester resin and fluorinated polyether polyimide resin solution into a reaction kettle according to the mass ratio, and stirring and mixing at 50° C. to obtain a resin matrix;

[0051] Addition of anticorrosive fillers and additives: Add nano-titanium dioxide, graphene, zinc powder, diphenylamine, ammonium polyphosphate and sodium polyacrylate to the mixed resin matrix according to the mass ratio and stir at 75°C for 1 hour;

[0052] Preparation of composite material component 1: slowly adding the pretreated mixed fiber into a resin matrix containing an anticorrosive filler and an additive, stirring at 20 r / min for 25 minutes to obtain composite material component 1;

[0053] Preparation of composite material component 2: adding m-phenylenediamine, benzoyl peroxide, pyromellitic dianhydride and aminosilane into the second reaction kettle according to the mass ratio and mixing them to obtain composite material component 2;

[0054] Post-processing: Degassing treatment is performed on the composite material component one and the composite material component two respectively.

[0055] When used for corrosion protection and reinforcement of power circulating water pipelines, the composite material component 1 and composite material component 2 prepared above are first fully blended in a mass ratio of 3:4 to form a mixed composite material. The prepared mixed composite material is then evenly sprayed onto the inner wall of the pipeline by spraying. The pipeline is then placed in a curing oven for curing at 200°C for 2 hours, until the thickness of the mixed composite material covering the inner wall of the pipeline reaches 5mm, thereby achieving pipeline reinforcement.

[0056] Comparative Example 1

[0057] No fluorinated polyether polyimide resin solution was added, and other components and preparation methods were the same as those in Example 1.

[0058] Comparative Example 2

[0059] A single epoxy resin was used as the resin matrix, and other components and preparation methods were the same as those in Example 1.

[0060] Mechanical properties test: According to GB / T1447-2005 "Test method for tensile properties of fiber reinforced plastics", the pipes coated with the corresponding composite materials in Examples 1 to 3 and Comparative Examples 1 and 2 were tested for tensile strength and flexural strength. The results are shown in Table 1.

[0061] Table 1 (Mechanical properties test results)

[0062] Group Tensile strength (MPa) Flexural strength (MPa) Example 1 620 780 Example 2 605 765 Example 3 615 775 Comparative Example 1 580 720 Comparative Example 2 480 600

[0063] The mechanical properties of Examples 1 to 3 were significantly superior to those of Comparative Examples 1 and 2. The Examples employed a composite matrix of multiple fibers for reinforcement and multiple resins, particularly the addition of a fluorinated polyether polyimide resin solution, significantly improving the tensile and flexural strengths of the material. Its rigid segments formed an interpenetrating network with the other resins, enhancing the overall mechanical properties of the matrix. Comparative Example 1 lacked the fluorinated polyether polyimide resin solution, resulting in lower mechanical properties compared to the Examples. Comparative Example 2, with its single epoxy resin matrix, exhibited insufficient strength and toughness.

[0064] Anticorrosion Performance Test: Pipe samples coated with the corresponding composite materials in Examples 1 to 3 and Comparative Examples 1 and 2 were immersed in a solution simulating power circulating water (containing 3% sodium chloride, microbial culture, etc.) for 30 days. The anticorrosion performance was evaluated by measuring the mass loss rate of the samples. The results are shown in Table 2.

[0065]

[0066] Table 2 (Anti-corrosion performance test results)

[0067] Group Mass loss rate (%) Example 1 0.5 Example 2 0.6 Example 3 0.55 Comparative Example 1 0.8 Comparative Example 2 2.5

[0068] The mass loss rates of Examples 1 to 3 were much lower than those of Comparative Examples 1 and 2, demonstrating the excellent corrosion resistance of the composite materials of the present invention. The fluorinated groups in the fluorinated polyether polyimide resin solution form a dense, low-surface-energy protective layer on the material surface, effectively blocking the penetration of corrosive media such as chloride ions and microorganisms. This layer, synergistically with nano-titanium dioxide, graphene, and zinc powder, provides enhanced corrosion protection from multiple chemical, physical, and electrochemical perspectives. Comparative Example 1 lacks the barrier and chemical corrosion resistance of the fluorinated polyether polyimide resin solution, resulting in a higher mass loss rate than the Examples. The single resin matrix in Comparative Example 2 exhibits poor corrosion resistance.

[0069] Temperature resistance testing: Samples were cyclically tested in a temperature range of -40°C to 150°C, maintaining each temperature for 2 hours. After three cycles, the appearance and performance of the samples were observed. The results showed that the composite materials prepared in Examples 1 to 3 showed no significant changes in appearance, with no surface defects such as cracks or blisters. The decrease in tensile and flexural strength was less than 3%. However, after the cyclic test, the sample in Comparative Example 1 developed fine surface cracks and saw a decrease in tensile and flexural strength of 8%. The sample in Comparative Example 2 showed more pronounced surface cracking, with a decrease in tensile and flexural strength of 15%. This shows that the composite material of the present invention further improves the high and low temperature resistance of the material by introducing a fluorinated polyether polyimide resin solution. The rigid imide ring and the fluorinated polyether segment with excellent weather resistance in its molecular structure can effectively resist the thermal stress damage caused by drastic temperature changes, so that the composite material can still maintain good structural stability and mechanical properties within a wide temperature range of -40°C to 150°C, better adapting to the complex temperature environment caused by ambient temperature fluctuations or medium temperature changes during the operation of the power circulating water pipeline, and significantly extending the actual service life and operational reliability of the pipeline.

[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. High-strength anti-corrosion power circulating water pipeline reinforcement composite material, characterized by: Calculated by mass, the composition comprises 40-60 parts of resin matrix, 30-50 parts of reinforcing fiber, 10-20 parts of anticorrosive filler, 0.5-1.5 parts of coupling agent, 5-10 parts of curing agent and 1-3 parts of auxiliary agent.

2. The high-strength anti-corrosion composite material for reinforcing electric power circulating water pipelines according to claim 1, characterized in that: The resin matrix is ​​a mixture of epoxy resin, vinyl ester resin, unsaturated polyester resin and fluorine-containing polyether polyimide resin solution, and the mass ratio is (2-3): (1-2): (1-2): (2-4).

3. The high-strength anti-corrosion composite material for reinforcing electric power circulating water pipelines according to claim 2, characterized in that: The preparation method of the fluorinated polyether polyimide resin solution comprises the following steps: adding a fluorinated polyether diamine monomer and a dianhydride monomer to N-methylpyrrolidone, stirring and reacting at 80-100° C. for 3-5 hours under nitrogen protection to obtain a polyamic acid solution; then heating the polyamic acid solution to 180-200° C. and performing an imidization reaction for 6-8 hours to obtain a fluorinated polyether polyimide resin; and finally dissolving the fluorinated polyether polyimide resin in N-methylpyrrolidone to obtain a fluorinated polyether polyimide resin solution. The mass ratio of the fluorinated polyether diamine monomer, the dianhydride monomer and the N-methylpyrrolidone is (1-2):(1.5-2):(1-2), and the mass ratio of the fluorinated polyether polyimide resin to the N-methylpyrrolidone is (1-2):(2-3).

4. The high-strength anti-corrosion composite material for reinforcing electric power circulating water pipelines according to claim 1, characterized in that: The reinforcing fiber is a mixture of glass fiber, carbon fiber and aramid fiber, and the mass ratio is (3-4):(1-2):(1-2).

5. The high-strength anti-corrosion composite material for reinforcing electric power circulating water pipelines according to claim 1, characterized in that: The anti-corrosion filler is a mixture of nano-titanium dioxide, graphene and zinc powder, and the mass ratio is (2-3): (1-2): (3-4).

6. The high-strength anti-corrosion composite material for reinforcing electric power circulating water pipelines according to claim 1, characterized in that: The curing agent is a mixture of an amine curing agent, a peroxide curing agent and a special curing agent for a fluorinated polyether polyimide resin solution, and the mass ratio is (1-3):(2-3):(1-2); the amine curing agent is m-phenylenediamine, the peroxide curing agent is benzoyl peroxide, and the special curing agent for a fluorinated polyether polyimide resin solution is pyromellitic dianhydride.

7. The high-strength anti-corrosion composite material for reinforcing electric power circulating water pipelines according to claim 1, characterized in that: The coupling agent is a silane coupling agent, which is one or both of aminosilane and vinylsilane; the auxiliary agent includes an antioxidant, a flame retardant and a dispersant; the antioxidant is a combination of one or more of diphenylamine, p-phenylenediamine and 2,6-tert-butyl-4-methylphenol; the flame retardant is a combination of one or more of magnesium hydroxide, ammonium polyphosphate and triphenyl phosphate; and the dispersant is a combination of one or more of sodium oleate, sodium polyacrylate and polyvinyl alcohol.

8. The method for preparing the high-strength anti-corrosion composite material for reinforcing electric power circulating water pipelines according to any one of claims 1 to 7, characterized in that: The following steps are involved: Fiber pretreatment: Mix glass fiber, carbon fiber and aramid fiber according to the mass ratio, soak them in 2-5% by mass silane coupling agent solution for 10-30 minutes, and dry them at 60-80℃ for 2-4 hours; Preparation of resin matrix: adding epoxy resin, vinyl ester resin, unsaturated polyester resin and fluorinated polyether polyimide resin solution into a reaction kettle according to the mass ratio, stirring and mixing at 40-60° C. to obtain a resin matrix; Adding anti-corrosion fillers and additives: Add nano titanium dioxide, graphene, zinc powder, antioxidant, flame retardant and dispersant to the mixed resin matrix according to the mass ratio, and stir at 60-80℃ for 1-2 hours; Preparation of composite material component 1: slowly adding the pretreated mixed fiber into a resin matrix containing an anticorrosive filler and an additive at a speed of 10-25 r / min for 10-30 minutes to obtain composite material component 1; Preparing the second composite material component: adding the curing agent and the coupling agent into the second reaction kettle according to the mass ratio and mixing them to obtain the second composite material component; Post-processing: Degassing treatment is performed on the composite material component one and the composite material component two respectively.

Citation Information

Patent Citations

  • High-strength anti-corrosion pipeline reinforcing composite material and preparation method thereof

    CN115820084A

  • Lightweight high-strength composite material

    CN119220053A

  • Aerogel modification-based solvent-free epoxy fireproof coating and preparation method thereof

    CN119823628A

  • Molding material, fiber-reinforced composite material, and manufacturing method of fiber-reinforced composite material

    JP2023140385A